Атрофия разума: Юрьев день Кирилла Серебренникова - Fedorushkov, Edyta (Studia Rossica Posnaniensia, 2021)
The article analyses the figure of the heroine Lubov in Kirill Serebrennikov’s film St George’s Day. The main aim is to show how the town of Yuriev and its residents affect the spiritual change of Lubov. The author examines the consistent rejection of the truth of the mind in favour of the truth of faith in Lubov’s life. The initial multilevel conflict between the opera singer and the town is supposed to be laid out in the Russian attitude to the world, which is based on the verge of two binary paradigms – the West and the East – exemplifying in turn the culture of the mind (reason) and the culture of faith (intuition). The provincial Russian town is correlated with the view of St. Petersburg in V. Toporov’s ‘Petersburg text’ due to its particular and distinguishable influence on outer visitors: the town imposes on Lubov its rules, affecting her present life not only materially but most of all spiritually. Besides, the consecutive analyses allow to draw an analogy between Lubov and Dostoevsky’s meek heroines. Like the ‘humiliated and insulted’ women of the author of Crime and punishment, the former opera singer enters the path of suffering and self-sacrifice to completely abandon her own self.